2016
DOI: 10.1080/02652048.2016.1194904
|View full text |Cite
|
Sign up to set email alerts
|

Separation and nanoencapsulation of antitumor peptides from Chinese three-striped box turtle (Cuora trifasciata)

Abstract: Chinese three-striped box turtle (Cuora trifasciata), as a freshwater turtle, is used as a tonic food. The purpose of this study was to isolate peptides with cancer growth inhibition activity from trypsin-digested hydrolysates of turtle proteins. The results demonstrated that two fractions T1 and T2 exhibited good inhibition on HepG-2 and MCF-7 cancer cells, with an inhibition of 70.65-89.1%, at 500 μg/mL. Subsequently, three peptides were identified from T1 and T2, including RGVKGPR (T1-1), KLGPKGPR (T1-2), a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 33 publications
0
6
0
1
Order By: Relevance
“…He et al (129) have reported antitumor peptides derived from the enzymatic hydrolysates of the Chinese three-striped box turtle (Cuora trifasciata). Two fractions, T1 and T2, inhibit HepG2 and MCF-7 cancer cells, and three peptides have been identified in these fractions: RgVKgPR (T1-1), KLgPKgPR (T1-2), and SSPGPPvH (T2-1).…”
Section: Amphibiansmentioning
confidence: 99%
“…He et al (129) have reported antitumor peptides derived from the enzymatic hydrolysates of the Chinese three-striped box turtle (Cuora trifasciata). Two fractions, T1 and T2, inhibit HepG2 and MCF-7 cancer cells, and three peptides have been identified in these fractions: RgVKgPR (T1-1), KLgPKgPR (T1-2), and SSPGPPvH (T2-1).…”
Section: Amphibiansmentioning
confidence: 99%
“…Recently, bioactive peptides derived from food proteins have been discovered with potent physiological activities such as antioxidant [ 11 ], anticancer, antibacterial, antifungal, and antitumor properties, as well as ion channel blockers, which opened a new standpoint for developing fatigue-relieving products [ 12 ]. Researchers have successfully isolated peptides possessing antifatigue potentials from aquatic organisms, e.g., sea cucumber, cod, hairtail and turtle [ 13 , 14 , 15 , 16 ]. The soft-shelled turtle ( Pelodiscus sinensis ) is a traditional Chinese nourishing food.…”
Section: Introductionmentioning
confidence: 99%
“…The powder did not affect ascites tumors in the mice, suggesting that it did not directly kill tumor cells and may act by activating the immune system [250]. Other studies on the antitumor activity of testudines' parts reported cytotoxic effects of the extract from the shell of the Greek tortoise Testudo graeca (Testudinidae) and of peptides isolated from enzymatic hydrolysates of proteins from the Chinese three-striped box turtle C. trifasciata to various animal and human carcinoma cell lines [251,252]. Furthermore, peptides from the Chinese softshell turtle P. sinensis altered microRNA expression in the AGS human gastric adenocarcinoma cell line involving, among others, upregulation of several tumor suppressor miRNAs [253].…”
Section: Cancer-immunomodulating Compounds From Testudinesmentioning
confidence: 99%